“PAMETHUK PARI” EKSPRESI MUSIKAL RITUAL PETHIK PARI DI DESA SUMBER ASRI KECAMATAN PURWOHARJO KABUPATEN BANYUWANGI JAWA TIMUR - Yatimin Yatimin; Santosa Soewarlan (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2020)
Pamethuk Pari, a Musical Expression of the Pethik Pari Ritual, is a form of music based on the ethnic Banyuwangi music using Angklung Paglak as a performance art. Interest in the existence of this ritual is becoming unknown in society. The phenomenon that occurs in the Pethik Pari ritual is rarely done in Banyuwangi Regency. The concept of art used is a symbolic concept with an arrangement concept that emphasizes new music with Banyuwangi ethnic music media. The initial steps in the process of creating a musical work Pamethuk Pari include 1) observation to determine the possible limitations to be packaged in a musical piece. Observations were made by looking for information that reviewed the Pethik Pari ritual, 2) Search for materials looking for instruments whose sound characters could represent rural nuances, 3) Collection of Materials, 4) Methods and Stages of Material Processing so that the links between the musical instruments could complement one another 5) Technical arrangement of materials by means of instrument exploration. The philosophy of the musical Pamethuk Pari contains guidelines for community life that teach mutual respect, togetherness, and gratitude to God Almighty.